Existence results for a multipoint fractional boundary value problem in the fractional derivative Banach space - Boucenna, Djalal (2022)
We study a class of nonlinear implicit fractional differential equations subject to nonlocal boundary conditions expressed in terms of nonlinear integro-differential equations. Using the Krasnosel'skii fixed-point theorem we prove, via the Kolmogorov-Riesz criteria, the existence of solutions. The existence results are established in a specific fractional derivative Banach space and they are illustrated by two numerical examples.